Pyrolysis temperature-dependent carbon retention and stability of biochar with participation of calcium: Implications to carbon sequestration - Nan, Hongyan; Yin, Jianxiang; Yang, Fan; Luo, Ying; Zhao, Ling; Cao, Xinde (Environmental pollution (1987), 2021)
Converting biomass waste into biochar by slow pyrolysis with subsequent soil amendment is a prospective approach with multiple environmental benefits including soil contamination remediation, soil amelioration and carbon sequestration. This study selected cow manure as precursor to produce biochar under 300 °C, 400 °C, 500 °C and 600 °C, and a remarkable promotion of carbon (C) retention in biochar by incorporation of exogenous Ca was achieved at all investigated pyrolysis temperatures. The C retention was elevated from 49.2 to 68.3% of pristine biochars to 66.1–79.7% of Ca-composite biochars. It was interesting that extent of this improvement increased gradually with rising of pyrolysis temperature, i.e., doping Ca in biomass promoted pyrolytic C retention in biochar by 16.6%, 23.4%, 29.1% and 31.1% for 300 °C, 400 °C, 500 °C and 600 °C, respectively. Thermogravimetric-mass spectrometer (TG-MS) and X-ray photoelectron spectroscopy (XPS) showed that Ca catalyzed thermal-chemical reactions and simultaneously suppressed the release of small organic molecular substances (C2–C7) via physical blocking (CaO, CaCO3, and CaClOH) and chemical bonding (CO and OC–O). The catalyzation mainly occurred at 200–400 °C, while the suppression was more prominent at higher temperatures. Raman spectra and 2D FTIR analysis on biochar microstructure showed that presence of Ca had negative influence on carbon aromatization and thus weakened biochar's stability, while increasing pyrolysis temperature enhanced the stability of carbon structure. Finally, with integrating “C retention” during pyrolysis and “C stability” in biochar, the maximum C sequestration (56.3%) was achieved at 600 °C with the participation of Ca. The study highlights the importance of both Ca and pyrolysis temperature in enhancing biochar's capacity of sequestrating C. [Display omitted] •Exogenous mineral Ca in pyrolysis could promote more carbon retained in biochar.•Extent of this promotion increased gradually with rising of pyrolysis temperature.•Biochar stability was determined by interaction of Ca and pyrolysis temperature.•Ca suppressed release of small molecules via physical blocking/chemical bonding.•Optimal carbon sequestration (56.3%) was achieved at 600 °C with Ca participation.